2005
DOI: 10.1016/j.visres.2005.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Optic-flow and egocentric-direction strategies in walking: Central vs peripheral visual field

Abstract: The impact of a central or peripheral visual field loss on the vision strategy used to guide walking was determined by measuring walking paths of visually impaired participants. An immersive virtual environment was used to dissociate the expected paths of the optic-flow and egocentric-direction strategies by offsetting the walker's point of view from the actual direction of walking. Environments consisted of a goal within a forest, the goal alone, or the forest alone following a brief presentation of the goal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 46 publications
3
63
0
3
Order By: Relevance
“…Visually guided locomotion has received considerable attention in the past [10,27,40,22,39,6], and two main strategies to move towards a goal have been identified. The first one, proposed by Gibson [10], leverages the optical flow created by the apparent motion of each point composing the sequence of images perceived by the walker during his motion [17].…”
Section: Goal-directed Locomotionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visually guided locomotion has received considerable attention in the past [10,27,40,22,39,6], and two main strategies to move towards a goal have been identified. The first one, proposed by Gibson [10], leverages the optical flow created by the apparent motion of each point composing the sequence of images perceived by the walker during his motion [17].…”
Section: Goal-directed Locomotionmentioning
confidence: 99%
“…The second strategy, proposed by Rushton [33], aims at aligning the locomotor axis with the perceived egocentric direction of the target to reach. Studies have shown that both strategies are used during locomotion steering [40], with a different predominance depending on the amount of available visual information [12,42,39].…”
Section: Goal-directed Locomotionmentioning
confidence: 99%
“…Left side picture is a frontal view of the goggles, while the right side picture is the participant's viewpoint through the goggles. of optic flow strategies, while the peripheral visual field is associated with egocentric direction strategies (Turano et al, 2005;Warren & Kurtz, 1992). In addition, common eye disorders among older adults involve impairments in one of these visual fields (Centers for Disease Control and Prevention, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Central and peripheral vision work synergistically to form the visual spectrum. Each visual field contributes different types of information for motion perception and locomotor control (Shapiro, Lu, Huang, Knight, & Ennis, 2010;Turano, Yu, Hao, & Hicks, 2005;Warren & Kurtz, 1992). The central visual field provides focal information advantageous for image contrast and displacement information but is limited to a small spatial area.…”
mentioning
confidence: 99%
See 1 more Smart Citation